The Philosophical Thought of Al-Jahiz - Mahmood Hamid, Assist. Lect. Najlaa (Basra studies journal, 2025)
This research aims to trace the impact of Al-Jahiz on the philosophical thought and intellectual development of the Arab and Islamic mind. Al-Jahiz serves as a key source for understanding this development from both intellectual and philosophical perspectives, while also providing a brief historical overview of the origins of Arab mentality. We argue that rational thinking did not emerge suddenly, but rather developed gradually, building stone by stone through different phases. The Holy Quran played a central role in fostering rational thinking, containing philosophical and universal theories that contributed to the growth of intellectual movements through contemplation, reflection, research, and the study of metaphysical realities in a systematic manner. We emphasize that the Mu’tazilite school of thought and its proponents were pioneers in this development, significantly shaping the rational trend. In this study, we focus on Abu Uthman Al-Jahiz to shed light on this intellectual progress, offering a general examination of the Mu’tazilite legacy. This includes their philosophical contributions beyond their well-known influence in poetry, literature, and rhetoric, with the aim of exploring a lesser-known aspect of their intellectual and philosophical impact. Al-Jahiz’s works stand as a testament to this significant cultural evolution.